Higher risk of phaeochromocytoma/paraganglioma (Phaeo‐Pgl) in SDHD than SDHB carriers: an Australian cohort study. Issue 4 (7th April 2019) - Hong, Alice; Shanahan, Mary; Schenberg, Tess; Inder, Warrick; MacIsaac, Richard; James, Paul; Sachithanandan, Nirupa
Abstract: Carriers of succinate dehydrogenase (SDHx) mutations are at risk of developing phaeochromocytomas, catecholamine secreting extra‐adrenal paragangliomas and non‐secretory head and neck paragangliomas and require lifelong surveillance. There is no current consensus on the optimal surveillance strategy. This study describes the outcomes of a cohort of 50 SDHx mutation carriers followed at a tertiary Australian hospital using a surveillance protocol involving annual clinical review with plasma/urine metanephrines and biennial magnetic resonance imaging from skull base to pelvis.